2021
DOI: 10.1186/s12890-021-01651-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-radiological predictive model in differential diagnosis of small (≤ 20 mm) solitary pulmonary nodules

Abstract: Background There is a lack of clinical-radiological predictive models for the small (≤ 20 mm) solitary pulmonary nodules (SPNs). We aim to establish a clinical-radiological predictive model for differentiating malignant and benign small SPNs. Materials and methods Between January 2013 and December 2018, a retrospective cohort of 250 patients with small SPNs was used to construct the predictive model. A second retrospective cohort of 101 patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These 20 studies (Table 1 ) included 5171 total SPNs (malignant: 3662; benign: 1509). PET/CT results were included in 7 of these studies [ 14 , 15 , 18 – 20 , 22 , 24 ], while 6 included tumor marker results [ 11 , 16 , 23 , 24 , 27 , 29 ]. Moreover, 10 studies had predictive models consisting of > 4 factors [ 14 – 16 , 20 , 21 , 23 – 27 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…These 20 studies (Table 1 ) included 5171 total SPNs (malignant: 3662; benign: 1509). PET/CT results were included in 7 of these studies [ 14 , 15 , 18 – 20 , 22 , 24 ], while 6 included tumor marker results [ 11 , 16 , 23 , 24 , 27 , 29 ]. Moreover, 10 studies had predictive models consisting of > 4 factors [ 14 – 16 , 20 , 21 , 23 – 27 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chae et al [14] achieved an AUC of 0.85 using deep learning for nodules 20 mm, while Zhang et al [15] reported an internal validation AUC of 0.85 for nodules ranging from 5-20 mm. In contrast, both Chen et al [11] and Zhao et al [12] externally validated their models, achieving AUC of 0.847 and 0.870 for nodule size 8-20 mm and 20 mm, respectively. Notably, these models target nodules of varying sizes, complicating direct performance comparisons with our MIFNN model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focusing on the diagnosis of small pulmonary nodules, including the nomograms proposed by Chen et al [11] and Zhao et al [12], as well as the machine learning models introduced by Zhang et al [13] and Chae et al [14], primarily address nodules smaller than 20 mm in diameter. Mao et al's work [15], in particular, targets nodules ranging from 6 to 15 mm.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where these nodules are > 6 mm in size, computed tomography (CT)-based routine follow-up is warranted [ 4 ], with a 1.1-fold increase in the risk of PN malignancy with each 1 mm increase in diameter [ 5 ]. Analyses of patient clinical data and CT imaging findings are the most commonly used approach to PN diagnosis [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CT features often indicative of PN malignancy include CT bronchus sign, vascular convergence sign, pleural retraction, lobulation, and spiculated sign [ 6 8 ]. Clinical risk factors for PN malignancy include more advanced age, elevated serum levels of tumor marker proteins, and a history of smoking [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%